Publication integrity viewed from different perspectives: a focus group study (Pubmet, 2022)
Publication and communication of research findings are important for the development of science, since future scientific work relies and builds on previous findings. However, this is not possible if researchers cannot trust the published work or if the principles of research integrity are not implemented in all phases of the research process, including the publication of research results (ALLEA 2017, NASEM 2017). This study aimed to explore authorship and publication practices across different disciplinary fields and to identify areas related to the publication of research findings that require improvements. We used a purposive sample strategy to recruit researchers from different disciplinary fields (humanities, social sciences, natural sciences, and medical sciences), different levels of seniority, and geographical locations. We conducted 30 focus groups with 174 researchers and other stakeholders from eight European countries (Belgium, Croatia, Denmark, Germany, Greece, Italy, Spain, and the Netherlands). The data will be analysed using the thematic analysis approach to develop a thematic map with themes and sub-themes. Currently, we are analysing the data using the NVivo software (QSR International). Some of the codes and sub-codes already identified are: 1) authorship distribution (authorship statement/plan; disciplinary field/country specifics and differences regarding authorship distribution/practices, ethical issues in authorship, handling authorship disputes); 2) authorship, publications, and academic career (stakeholders’ evaluation of authorship and publications); 3) research publication and dissemination (examples of good publication practices, examples of issues related to publication process); 4) peer review (good peer review practices, poor peer review practices); and 5) open science (perceptions on open science; open access, open data, open collaboration, and reproducible research).One possible limitation of our study, taking into account that publication practices differ significantly in different settings (countries, fields, etc.), could be that the knowledge obtained could not be generalised and applied globally, since we included participants from European countries alone. However, we believe that by including a large number of participants we managed to map publication practices in the European area and will be able to learn what should be improved and how to foster good publication practices by European researchers.